Environmental justice and the new pluralism : the challenge of difference for environmentalism - Schlosberg, David (Oxford ; New York : Oxford University Press, 1999)
In this theoretical treatment of the environmental justice movement, David Schlosberg demonstrates the development of a new form of critical pluralism. His study presents a challenge to both conventional pluralist thought and the practices of the major groups in the US environmental movement.
pt. 1. Environmentalism and difference : the pluralist challenge -- 1. Introduction : the environmental challenge to pluralism -- 2. Approaches to difference in the US environmental movement : classification schemes, hegemonic definitions, and singular motivations -- pt. 2. Critical pluralism in theory -- 3. Pluralism and difference : a genealogy of multiplicity -- 4. Components of a critical pluralism : ethics and processes -- pt. 3. Environmental justice : critical pluralism in practice -- 5. The politics of networking in the grassroots environmental justice movement -- 6. Communicative practices and communicative demands in the environmental justice movement -- pt. 4. Conclusion -- 7. Environmental justice and the prospects for a critical pluralism.
Includes bibliographical references (pages 195-217) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Environmental justice -- United States; Environmental policy -- United States; Environmentalism -- Political aspects -- United States; Cultural pluralism; Cultural Diversity; Justice environnementale -- États-Unis.; Environnement -- Politique gouvernementale -- États-Unis.; Environnementalisme -- Aspect politique -- États-Unis.; Diversité culturelle; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Cultural pluralism; Environmental justice; Environmental policy; Environmentalism -- Political aspects; United States